2011
DOI: 10.1186/1743-422x-8-343
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of human cytomegalovirus co-infection in Egyptian chronic HCV patients

Abstract: Human cytomegalovirus (HCMV) is the most common cause of severe morbidity and mortality in immune- compromised individuals. This study was conducted to determine the incidence of HCMV infection in HCV patients who either spontaneously cleared the virus or progressed to chronic HCV infection. The study included a total of eighty four cases (48 females and 36 males) that were referred to blood banks for blood donation with an age range of 18-64 years (mean age 37.62 ± 10.03 years). Hepatitis C virus RNA and HCMV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
(32 reference statements)
6
14
1
Order By: Relevance
“…HCV is responsible for infecting over 20 million in Arab countries (3). The prevalence of that virus is reported to be higher in Egypt than in any other Arab country; the prevalence of HCV among the general populations is variable from 13 to 22% [4]. It is found to be 14.5% among blood donors, 7.7% among healthcare workers, and 47.2% in chronic liver disease patients [5].…”
Section: Introductionmentioning
confidence: 98%
“…HCV is responsible for infecting over 20 million in Arab countries (3). The prevalence of that virus is reported to be higher in Egypt than in any other Arab country; the prevalence of HCV among the general populations is variable from 13 to 22% [4]. It is found to be 14.5% among blood donors, 7.7% among healthcare workers, and 47.2% in chronic liver disease patients [5].…”
Section: Introductionmentioning
confidence: 98%
“…We are aware of only one small study that examined the association of HCV infection with measures of the immune response against CMV [16]. The results of that study showed that both CMV seroprevalence and CMV IgG levels differed by HCV infection status [16]. An important limitation of that study, though, aside from its small sample size was that age and other potentially confounding factors were not accounted for in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of only one small study that examined the association of HCV infection with measures of the immune response against CMV [16]. The results of that study showed that both CMV seroprevalence and CMV IgG levels differed by HCV infection status [16].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fact that HCMV viruses contribute an immunomodulatory effect resulting in developed of immunosuppression 43,44 and dysregulation of cytokine which could fast HCV pathogenesis of patients in critical condition. 39 CMV infection promotes HCV pathogenesis by prohibition the normal mechanisms responsible for HCV elimination, thus playing vital role in HCV existence and pathogenicity. 45 …”
Section: Discussionmentioning
confidence: 99%
“…37 Bayram et al 38 was shown that CMV was diagnosed in HBV or HCV patients as a dual infection and that it can increase the risk of the disease. In Egypt, Tabll et al 39 were examined the potential role thatCMV plays in chronic HCV progression. Also Bader El din et al, 40 demonstrate higher rate of CMV co-infection in chronic HCV patients in Egypt than other patient populations.…”
Section: Discussionmentioning
confidence: 99%